2013
DOI: 10.1128/aem.02797-12
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Conversion Inhibitors Furfural and 5-Hydroxymethylfurfural Induce Formation of Messenger RNP Granules and Attenuate Translation Activity in Saccharomyces cerevisiae

Abstract: Various forms of stress can cause an attenuation of bulk translation activity and the accumulation of nontranslating mRNAs into cytoplasmic messenger RNP (mRNP) granules termed processing bodies (P-bodies) and stress granules (SGs) in eukaryotic cells. Furfural and 5-hydroxymethylfurfural (HMF), derived from lignocellulosic biomass, inhibit yeast growth and fermentation as stressors. Since there is no report regarding their effects on the formation of cytoplasmic mRNP granules, here we investigated whether fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 40 publications
(90 reference statements)
2
35
0
Order By: Relevance
“…Comprehensive analyses of the inhibitory mechanisms of furfural, 5-HMF, and acetic acid on yeast growth and fermentation 8) 10) have shown that more genes are down-regulated than up-regulated in the presence of these compounds 8) . In addition, the translational activity of furfural-treated S. cerevisiae cells is lower than that of untreated cells 11) . The genes downregulated in the presence of furfural are involved in the expression of metabolic enzymes 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive analyses of the inhibitory mechanisms of furfural, 5-HMF, and acetic acid on yeast growth and fermentation 8) 10) have shown that more genes are down-regulated than up-regulated in the presence of these compounds 8) . In addition, the translational activity of furfural-treated S. cerevisiae cells is lower than that of untreated cells 11) . The genes downregulated in the presence of furfural are involved in the expression of metabolic enzymes 8) .…”
Section: Introductionmentioning
confidence: 99%
“…HMF induce genotoxic effects in microorganisms by reducing enzymatic and biological activities, breaking down DNA, inhibiting protein and RNA synthesis, and are considered among the most potent inhibitors (Liu et al 2004). Also, HMF inhibit the growth of yeast cells and subsequent fermentation in a dose-dependent manner (Iwaki et al 2013). HMF can be bioactivated to the mutagenic compound, 5-sulphoxymethylfurfural (SMF) (Husøy et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Component proteins are basically different, although partially shared. Component factors vary with the kinds of stresses encountered (Hoyle et al 2007 ;Buchan et al , 2011Kato et al 2011 ;Yamamoto and Izawa 2013 ). SGs are composed of untranslated mRNA, the translation initiation factor, eIF, poly (A) binding protein, and 40S ribosomal protein (Balagopal and Parker 2009 ; ).…”
Section: Translational Repression P-bodies and Stress Granulesmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , the formation of P-bodies is fi rst induced in response to stress . The formation of yeast SGs is induced by more stressful conditions or the passage of time Kato et al 2011 ;Yamamoto and Izawa 2013 ). The formation of P-bodies in yeast was previously reported to be regulated by Ras/PKA activity and protein kinases, such as Pkh1/Pkh2 and Pkc1 (Luo et al 2011 ;Ramachandran et al 2011 ).…”
Section: Translational Repression P-bodies and Stress Granulesmentioning
confidence: 99%